Compostos bioativos de pereskia aculeata: estudo de clones para melhoramento genético e dos efeitos das técnicas de preparo culinário - Neves, Bruna Vitoria [UNIFESP] (2018)
Ora-pro-nobis is an unconventional food plant - PANC that is widely distributed and easy to grow, besides being a good alternative food. Due to its potential consumption, EMBRAPA has invested in the development of clones, being important the evaluation of the composition in nutrients and bioactive compounds of these, to allow selection and that producers and consumers have an advantage in their production and consumption, respectively. We know that the technique of cooking applied in the preparation of food can contribute favoring the availability of nutrients and bioactive compounds. The objective of this study was to evaluate the bioactive compounds present in different clones of Pereskia aculeata produced by EMBRAPA Hortaliças - Brasília-DF, and to evaluate the effect of preparation techniques - microwave, steamed, and stir-fryer - on the bioactive compounds contents of Pereskia aculeata cultivated in Amparo - SP. The quantification of carotenoids, phenolic compounds and vitamins were determined by high performance liquid chromatography (HPLC), and antioxidant activity by ORAC and ROO * methods. The clones that presented the best results were 20 and 28 for phenolic compounds (2.71±0.05mg GAE/100g and 2.29±0.10 mg GAE/100g respectively), clone 20 had a better result for ascorbic acid (33.26± 8.87mg/100g) and for total carotenoids the clones 01, 08, 10 and 25 (25889.40±12.14μg/100g, 21016.50±34.63μg/100g, 21796.90±27μg/100g; 26346.15±14.39μg / 100g in this order). A total of 13 carotenoids were identified, with the majority of all-trans-lutein and all-trans β carotene, the highest amount of total carotenoids detected in raw ora-pro-nobis leaves (4647.82±122.1μg/100g) and cooked in microwave (5556.32±245.3μg/100g), microwave cooking was also the one that obtained a better response for both analyzes of antioxidant activity, ORAC and ROO * (89.82±4.34μmol TE/g and 7,28μmol α-tocopherol/g), respectively. 14 phenolic compounds were identified; cooking under steamed (11.46 ± 0.54 mg GAE/100 g) was the best kept in the presence of these compounds; the vitamins presented different responses for each technique of applied cooking, ascorbic acid and thiamine had better (0.83±0.14mg/100g and 1.18±0.37mg/100g), respectively, when the pyridoxine, pantothenic acid and biotin with vitamins were kept in a higher amount (0.08 ± 0.03mg/100g) cooking also shows a significant value for pantothenic acid 1.23± 0.32 mg/100g, when cooked in the microwave the amount of (0.06±0.01mg 100g) pyridoxine approaches the one found when stir frying (0.08± 0.03). The clone that had the best response for the analyzes was the 20 for phenolic compounds and ascorbic acid, for carotenoids clones 01, 08, 10 and 25 had a better result. The best cooking technique applied was microwave cooking, which kept the highest amount of the bioactive compounds for ora-pro-nobis. The challenge of determining the best way to consume bioactive compounds to promote their beneficial health properties is for researchers around the world, since the purpose of research is to generate scientific information with direct application in the daily lives of the general population.